Labor Unrest in the Ready-Made Garment Industry of Bangladesh : Causes and Consequences - Choudhury, Sabbrina; Rahman, Md. Habibur (European Scientific Journal, ESJ, 2017)
Labor unrest is a very recurrent circumstance in the garment’s industry of Bangladesh. Violent protest and agitation by workers has become a common feature in garment’s industry. So take into account, we examine the main causes and consequences behind the labor unrest of Ready-Made Garment (RMG) industry in Bangladesh. Data for the study was collected from different garment factories of Dhaka, Ashulia, Tongi, Mirpur, Mohakhali, Gazipur, Narayangang and Savar. Face to face interview and questionnaire method have been used for collecting data of this study. The findings show that the low wage and long working hour are the main causes of labor unrest in the RMG industry of Bangladesh that, in turn, create job dissatisfaction. If the policy makers of RMG industry consider these causes and consequences and take required steps to overcome these problems, the labor unrest in garment industry will be eliminated. Additionally, we identify future research areas that provide scholars opportunities to push theoretical boundaries and offer further insights into the labor unrest